Hubungan Jenjang Pendidikan terhadap Perilaku Menjaga Kesehatan Gigi dan Mulut Anak Tunagrahita di SLB Kota Sidoarjo - Dianita Rahmah Julia; Ristya Widi Endah Yani; Roedy Budirahardjo (Pustaka Kesehatan, 2018)
Intellectual disability is a child who suffers from intellectual ability below average and tends to have retardation in intelligence, physical, emotional, and social. They are not independent enough in keeping their own health especially oral hygiene, it can affect their oral health behavior. Education that is one of external factors influences health behavior. Education and knowledge influence each other so that people are expected to have high education in order to be knowledgeable especially in terms of maintaining health. The purpose of this study was to analyze the correlation between education level and oral health behavior of children suffering from intellectual disability. This research was an observational analytic research with cross sectional approach. The subjects of this study were a number of children of SDLB, SMPLB and SMALB in SLB Sidoarjo, with total sampling as many as 115 students. The subjects were asked to fill out a questionnaire of knowledge and attitude how to brush teeth and performed the action as well. The collected data were analyzed by using spearman correlation test. The result of this research showed that correlation coefficient for education level with knowledge, attitude and behavior was > 0,05, so there was no relation between those variables. Meanwhile, the result of correlation coefficient of education with action was < 0.05, so there was correlation between those two. The conclusion of this research is there is no correlation between the level of education and oral health behavior of intellectual disability children in SLB Sidoarjo. Keywords: Mental retarded, dental health behavior, education level